UPAYA PENINGKATAN HASIL BELAJAR MELALUI METODE PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER PADA MATERI PELUANG - Sutopo; Widowati, Iris Prima; Novianti, Idha (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
The purpose of this study was to determine the increase in learning outcomes of opportunity material through the numbered head together (NHT) cooperative learning method in class VIII students. Factors that cause low student learning outcomes on opportunity material include students not reading and understanding the concept of opportunity material, not doing enough practice questions, difficulty describing the sample space, arranging events in an experiment, understanding the principles of events in an experiment. This research was conducted by applying the first four steps in each cycle, namely planning, action, observation, reflection. The results showed that using the numbered head together (NHT) type of cooperative learning method can improve student learning outcomes, especially in the matter of opportunities. This can be seen through the results of the analysis of teacher activity using the NHT type of cooperative learning which has increased from cycle I and cycle II by 14%. The results of the analysis of student activities using the NHT cooperative learning type experienced an increase from cycle I and cycle II in the interest value of 10%, the value of attention 15%, and the value of cooperation 10%. The results of the analysis of student learning outcomes tests in cycle I obtained 6 students who were included in the incomplete category and 10 students who were included in the complete category, while in cycle II it was obtained 2 students who were included in the incomplete category and 14 students who were included in the complete category.